1999
DOI: 10.1210/jcem.84.1.5531
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of Estrogen Receptor-β Immunoreactivity in Human Growth Plate Cartilage

Abstract: Estrogens affect longitudinal bone growth through their action on endochondral bone formation. Two estrogen receptors are known, the classical estrogen receptor-alpha (ER alpha), newly demonstrated in human growth plate cartilage, and a recently cloned estrogen receptor-beta (ER beta). The present study aimed to localize a possible expression of ER beta protein in human growth plates. Tissue samples were obtained from tibial and femoral growth plates in four female pubertal patients undergoing epiphyseal surge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
10
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(12 citation statements)
references
References 0 publications
2
10
0
Order By: Relevance
“…Our results indicate that both receptor types are present in an identical distribution within the distinct zones of the growth plate. In accordance with the results of Nilsson et al [14]our data suggest that the zone of hypertrophic chondrocytes is the major site of action for estrogens within the growth plate.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our results indicate that both receptor types are present in an identical distribution within the distinct zones of the growth plate. In accordance with the results of Nilsson et al [14]our data suggest that the zone of hypertrophic chondrocytes is the major site of action for estrogens within the growth plate.…”
Section: Discussionsupporting
confidence: 93%
“…Detection of ER in bone and cartilage has been problematic in earlier studies, partly due to the low expression of ER in these tissues when compared to classical estrogen target tissue like the urogenital tract [10, 11]. Studies on intact tissue in the human growth plate are sparse and limited to the investigation of one of the two receptor types [12, 13, 14]. Whereas ER-α was detected in all zones of the growth plate by in situ hybridization and immunohistochemistry by Kusec et al [13], ER-β was only reported to be present in hypertrophic chondrocytes in an immunohistochemical study by Nilsson et al [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These receptors are commonly referred to as ER␣ and ER␤, and their expression has been described previously in skeletal cells (14)(15)(16)(17)(18)(19)(20). In humans, evidence for the importance of ER␣ for mediating effects of estrogen in the skeleton comes from a case report describing a young male with estrogen resistance caused by a mutation in the human ER␣ gene (21).…”
mentioning
confidence: 99%
“…All three sex steroid receptors are expressed both in growth-plate cartilage and in bone (6)(7)(8)(9)(10)(11). Functional studies using sex steroid receptor-inactivated animal models have demonstrated that ER␣ but not ER␤ is important for the regulation of appendicular longitudinal skeletal growth in male mice (12)(13)(14), and a recent report indicates that AR-inactivated male mice have unaffected bone length (15).…”
mentioning
confidence: 99%